Penerapan Core Vocabulary Approach pada Anak dengan Celah Bibir dan Langit-langit - jumiarti; Damarrulah (Jurnal Terapi Wicara, 2025)
Background: Children with cleft lip with or without cleft palate are at risk for speech disorders, including resonance and speech sound errors. These speech difficulties may significantly impact comprehension and expressive abilities, potentially affecting psychological well-being, quality of life, and social participation.Objective: This study aims to determine the effectiveness of the core vocabulary approach in improving articulation abilities for the phoneme /p/ at the word level.Methods: A single-case experimental design with a single-subject pattern was employed. The participant was a 2-year-9-month-old boy with a history of bilateral complete cleft lip and palate repair. Phase A1 (baseline 1) was conducted to record the participant’s articulation of the phoneme /p/ prior to intervention. Phase B (intervention) involved four structured therapy sessions using the core vocabulary approach. Phase A2 (baseline 2/withdrawal) was carried out by temporarily discontinuing the intervention to evaluate changes in articulation performance. Quantitative data were collected in the form of percentage accuracy of /p/ production in target words.Results: The findings showed no improvement in the accuracy of /p/ production across the four intervention sessions.Conclusion: These results are insufficient to support the core vocabulary approach as an effective therapeutic strategy for improving articulatory clarity in children with cleft lip and palate, particularly for bilabial plosive phonemes.